Dosimetric evaluation of field parameters in VMAT for cervical cancer with inguinal lymphatic drainage extension - Jing Zeng; Jinlong Hao; Jianguo Zhao; Peisong Sun (Scientific Reports)
Abstract For cervical cancer radiotherapy, patients requiring inguinal lymphatic drainage (ILD) extension fields pose challenges due to the large and complex target volume. To investigate the dosimetric effects of x-jaw width, jaw aperture position, and the number of arcs on volumetric modulated arc therapy (VMAT) plans for ILD extension fields, in order to optimize treatment planning. Thirty-nine patients were retrospectively included, and seven VMAT planning groups were created: OF (open field), X = 15/16/17/18 (jaw widths of 15–18 cm), SP (split-field, four arcs), and X = 15 M (jaw aperture moved toward the isocenter). Dosimetric parameters, including homogeneity index (HI), target coverage, and organs-at-risk (OARs) doses, were compared. The X = 15 plan achieved significantly lower intestinal, bladder, and rectal doses compared to the X = 17 and X = 18 plans (p < 0.05). The SP plan demonstrated superior HI and OARs sparing compared to the X = 15 plan, but required longer treatment times. The X = 15 M plan resulted in reduced edge doses but increased intestinal and bladder doses. For cervical cancer ILD extension fields, dual-arc VMAT plans with a 15 cm jaw width (X = 15) are recommended for optimal balance between target coverage and OARs sparing. Split-field plans may be considered if extended treatment time is acceptable.